(untitled) (Sebha University Conference Proceedings, 2025)
Photovoltaic panels sometimes produce excess power and at other times insufficient energy. To address this uncontrolled production, a storage system is essential. In this paper, pumped hydroelectric storage (PHS) is preferred as an energy storage system due to its ecological benefits and relevance to the context. Managing the energy of a PV/DG/PHS hybrid system requires specific control that considers the temporal availability of solar energy, optimizing diesel fuel consumption in real-time, and accommodating pumping constraints. The proposal showcases the efficiency of the PHS double effect system in terms of irrigation and electricity generation, while also highlighting fuel savings and a decrease in CO2 emissions. This research validates the new, precise method for calculating online fuel consumption per kWh, outperforming previous studies, and successfully tested within the suggested energy management system. The approach can be utilized in similar future research efforts.